2020
DOI: 10.1002/cam4.2881
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic low‐dose aspirin treatment on tumor prevention in three mouse models of intestinal tumorigenesis

Abstract: Although early detection and treatment of colorectal cancer (CRC) have improved, it remains a significant health‐care problem with high morbidity and mortality. Data indicate that long‐term intake of low‐dose aspirin reduces the risk of CRC; however, the mechanisms underlying this chemopreventive effect are still unclear. Different mouse models for inflammation‐associated, sporadic, and hereditary CRC were applied to assess the efficacy and mechanism of low‐dose aspirin on tumor prevention. An initial dosing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 52 publications
0
28
0
1
Order By: Relevance
“…Aspirin dosing in our CD1 Nude mouse model [ 36 , 37 ], which mimicked low-dose aspirin use in humans, based on profound platelet COX-1 inhibition but an absence of systemic COX-2 inhibition, did not increase the sensitivity of MC38 mouse CRC cell tumours to EPA in vivo, in direct contrast to the corresponding in vitro data. We demonstrated that there was inefficient inhibition of PGE 2 production in CRC cell tumour tissue, despite efficient systemic COX-1 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Aspirin dosing in our CD1 Nude mouse model [ 36 , 37 ], which mimicked low-dose aspirin use in humans, based on profound platelet COX-1 inhibition but an absence of systemic COX-2 inhibition, did not increase the sensitivity of MC38 mouse CRC cell tumours to EPA in vivo, in direct contrast to the corresponding in vitro data. We demonstrated that there was inefficient inhibition of PGE 2 production in CRC cell tumour tissue, despite efficient systemic COX-1 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…The developed targeted proteomics method was applied to characterize COX‐2 abundance in parallel to COX activity in three human colon carcinoma cell lines HCT‐116, HT‐29, and HCA‐7. Because of the central role of COX‐2 in colorectal cancer [ 7,47 ] it is interesting to study the ARA cascade in these cells producing different levels of prostanoids (Figure 3Ai,ii; Table S7, Supporting Information). Among the investigated compounds (ARA‐derived prostanoids), PGE 2 and 12‐HHT showed the highest levels and were detectable in all cell lines and may therefore serve as indicators of COX activity.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] Although constitutive COX‐2 (derived from the PTGS2 gene) expression is found in few tissues (e.g., brain), its expression is mainly regulated by growth factors, cytokines (such as tumor necrosis factor α or interleukin 1β) and pro‐inflammatory stimuli, for example, through the NFκb‐pathway. [ 6 ] Elevated COX‐2 gene expression has been reported in colon and several other cancers [ 7,8 ] as well as during diseases that are accompanied by chronic inflammation such as atherosclerosis. [ 9 ] This central role of COX‐2 in the mediation of inflammatory responses has made it a major target for drug development in the past years.…”
Section: Introductionmentioning
confidence: 99%
“…As an inhibitor of cyclooxygenase (COX)-1, aspirin exerts its significant chemo-preventive effects in CRC through inhibition of NF-κB dependent pathways, Wnt/β-catenin signaling, and additional COX proteins acetylation ( 150 , 151 ). The notable anti-tumor effects of aspirin have been observed by reduction in platelet activation, inhibition of tumor angiogenesis, and decrease of pro-inflammatory agents ( 152 ). In addition, low-dose aspirin could reduce metastasis in colon cancer, mainly due to its effective inhibition of prostaglandin E2 (PGE2) formation and platelet-tumor cell aggregation ( 153 ).…”
Section: Roles Of Inflammation and Scfas In The Context Of Cancermentioning
confidence: 99%